A brain metastasis therapy tweak, for the better? Concomitant stereotactic radiotherapy and molecular-targeted therapy - Soto, M; Larkin, J; Andreou, K; Karali, C; Sibson, N (Oxford University Press, 2017)
The most common cause of cancer demise is the metastasis to distant organs. In particular, brain metastasis represents one of the highest mortality rates in the oncology field. Some of the reasons for the meagre advance in the treatment of this disease are the limited conditions for favourable surgical debulking of tumour, off-target effects of conventional treatments and the limited efficacy of delivery into the brain for currently available drugs. Contrary to those conventional strategies, targeted anticancer therapies exploit molecules that act on specific mechanisms that may disturb the malignant process, whilst minimising adverse effects on healthy tissues. Based on that approach, we have been working on novel anti-cell adhesion molecule (CAM) therapies.